Structure and mechanical properties of a FeCoCrNi high-entropy alloy fabricated via selective laser melting - Lin, Danyang; Xu, Lianyong; Han, Yongdian; Zhang, Yankun; Jing, Hongyang; Zhao, Lei; Minami, Fumiyoshi (Intermetallics, 2020)
The relative density of high-entropy alloys fabricated with selective laser melting (SLM) was enhanced via a process optimization method based on polynomial regression analysis. The resulting alloy exhibited a high relative density (99.71%) and excellent tensile properties (tensile strength = 720 MPa; post-fracture elongation = 31.85%). Optimization has been more commonly based on volumetric energy density (VED), but the unreliability of this method has been evidenced by the large difference in relative densities achieved using the VED-based approach. The high strength of alloy samples was investigated based on structural characterization, and the formation mechanisms of various defects are discussed. There is no micro-segregation or secondary phase according to both theoretical calculations and experimental observation. The strengthening mechanism of SLM FeCoCrNi sample has been reported by quantitative analysis of dislocation strengthening and fine grain strengthening. It was found that the dislocation strengthening contributed more than fine grain strengthening to the increased yield strength in SLM. This deeper insight into the processing and the strengthening mechanisms is expected to contribute to improved mechanical properties of SLM products, thereby increasing the potential for industrial applications of SLM. [Display omitted] •Conventional process optimization based on VED is inaccurate.•SLM process optimization based on a polynomial regression model was proposed.•A relationship between the parameters, mechanisms and defects was established.•The large contribution of high dislocation density to yield strength was quantified.